Analisis Penerapan Akuntansi Zakat (PSAK 109) Pada Lembaga Amil Zakat Badan Amil Zakat Nasional (Baznas) - Azyumardi Azra; Arsa Arsa; Laily Ifazah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to understand the application of zakat accounting at LAZ BAZNAS Jambi City, to identify the obstacles in implementing zakat accounting at LAZ BAZNAS Jambi City, and to determine the suitability of the zakat accounting application at LAZ BAZNAS based on PSAK No. 109. This research uses a qualitative descriptive method, with data collected through interviews. The results of the study indicate that, first, the application of zakat accounting at BAZNAS Jambi City—based on the elements of recognition, measurement, and disclosure—has been implemented in accordance with PSAK No. 109. In terms of presentation, BAZNAS Jambi City provides cash flow financial reports, and the amil section is also included in the fund change report. Second, the obstacles faced by BAZNAS Jambi City include inefficiency in the distribution process in terms of time and energy, and the inability to use banking accounts. Other challenges are related to the lack of understanding and skills among human resources, the complexity of transactions, and insufficient government support to enable cooperation with banks, which would facilitate the distribution of zakat funds. Third, the conformity of zakat accounting application at BAZNAS Jambi City has been generally appropriate. However, in the presentation of financial statements, there are no changes in managed assets and no notes to the financial statements. Therefore, in terms of conformity, the financial statements of BAZNAS Jambi City are not yet fully in accordance with PSAK No. 109.